Qualidade dos Núcleos de Esporte e Lazer e sua associação com o perfil e o nível de atividade física dos frequentadores em São José dos Pinhais, Paraná - Custódio, Iazana Garcia (2019)
Aim: To analyze the association between the quality of the Sports and Leisure Centers with the profile and the level of physical activity of the participants in São José dos Pinhais, Paraná. Methods: Quantitative, observational study of cross - sectional design. The study was carried out in São José dos Pinhais, a municipality in the metropolitan region of Curitiba-PR. Ten Sport and Leisure Centers were selected to evaluate quality and use. The quality of the public spaces was collected through systematic observation of the environment, with the instrument Physical Activity Resource Assessment (PARA) translated and adapted version for the Brazilian context and the index of quality obtained following a version adapted in the literature, from the summation of the items that make up the instrument, data collection took place between March and July 2018. The evaluation of the use profile was done through systematic observation using the System for Observing Play and Recreation in Communities (SOPARC) . The collections were carried out on four days of the week (Tuesday, Wednesday, Saturday and Sunday), in four schedules (8:00 a.m. to 9:00 p.m.; 10:00 a.m. to 11:00 a.m.; : 00 hrs; 16: 00-17: 00 hrs), each time four observation moments were realized, one every 15 minutes, by target area, between the months of July and August. All descriptive (absolute and relative frequency) and analytical (ChiSquare, Anova One-Way and Kruskal-Wallis tests) were conducted in statistical software: Statistical Package for Social Sciences (SPSS) version 20.0 and Data Analysis and Statistical Software (STATA) with the level of significance held at 5%. Results: On average, the ten cores had a quality score of 65 points. The profile of the attendees observed in the Sports and Leisure Centers are mostly men (58.3%), adults (38.3%), non-blacks (97%). About 90% of the participants were observed to perform some activity and when stratified by level, most were observed in activities of moderate level or walking (38.2%). The female and the adult age and the elderly were positively associated with the high-quality Sports and Leisure Centers. The level of sedentary physical activity was inversely associated with the high quality of the Centers. Conclusions: These results are important so that public managers can direct specific and more effective resources and actions to promote physical activity.